Assessing the Effectiveness of National Service Scheme: Exploring the Perceptions of Service Personnel in the Sunyani Municipality of Ghana - Arthur, Jones Lewis; Amofah, Kwaku; Owusu-Banahene, Abigail (International Review of Management and Marketing, 2016)
The study assessed the perception of service personnel on the effectiveness of the national service scheme in the Sunyani Municipality, Ghana. One hundred National Service Persons out of the 1523 service persons deployed in 2013/2014 service year to the Sunyani Municipality were used for the study. A random sampling method (use of the simple lottery method) was used to select the sample. The study indicated that majority (74%) of the service persons got posted to stations of their choice but, 31% disagreed. The relevance of doing national service is dependent on the satisfaction with place of posting and opportunity to explore and exhibit one's full potential in the service as indicated by (Pearson Chi-square = 62.443, P < 0.05) and (Pearson Chi-square = 86.162, P < 0.05) respectively. Seventy-two (72%) of the service persons were given orientation before the commencement of their service and 74% stated that their allowance have been paid to date. The benefits gained from undertaking national service is dependent on how service persons rated their performance at work (Pearson Chi-square = 27.000, P < 0.05). Majority of the service persons were of the opinion that they were not assisted by the Municipal Director of national service to secure accommodation. Placement of service persons should be done in close consultation with the service persons, user agencies, as well as the developmental need of the nation. In this wise, a multi-stakeholder consultation is relevant because, it will ensure the satisfaction of the needs of all parties especially the service persons. A well-coordinated and widely consulted approach to national service will ensure that the needs of service persons such as transport, proper placement, provision of accommodation and transport are met to reduce the ever-reoccurring challenges that face the service scheme during each service year. Keywords: National Service, Perception, Effectiveness JEL Classifications: MOO, M1